Sarekat Islam: Gerakan Islam Modernis atau Tradisional? - Arif Rahim (Jurnal Ilmiah Dikdaya, 2020)
This paper discusses the position of Sarekat Islam (SI) as the largest and one of the most important organizations during the National Movement of 1900-1942, in the context of two large currents of Indonesian Islamic thought, namely traditional Islam and modernist Islam. Many historical works that do not explicitly explain the position of SI to the two groups have caused dissent. Through searching historical data about the 1912 Statutes and the speeches of SI leaders in the Bandung congress in 1916 it can be concluded that SI is an Islamic movement organization with a modernist style of Islam. However, this organization is less involved in the disputes between the reformers (Young People) and the traditions (Old People) compared to organizations that limit themselves in the social and educational fields.